Is There an Association between Bell Palsy in Pediatric Patients and COVID-19? - El-Deeb, Mohamed E.; Elzayat, Saad; Salamah, Abeer; Gamal, Ali; Elgamal, Shimaa; El-Sobki, Ahmed (International Archives of Otorhinolaryngology, 2025)
Introduction Bell palsy (BP) is an acquired, idiopathic facial palsy linked to lower motor neuron malfunction of the seventh cranial nerve. Several studies have identified BP as one of the many neuropathies that coronavirus disease 2019 (COVID-19) patients have developed, while other studies disagree.Objective To study if there is an association between BP in pediatric patients and COVID-19, and to examine the pattern of recovery in all pediatric cases of BP during the COVID-19 pandemic.Methods We performed a prospective cohort study on pediatric patients with acute onset unilateral facial weakness of unknown etiology (BP) during the pandemic period. All included patients were submitted to a reverse transcription-polymerase chain reaction (RT-PCR) test through nasopharyngeal and oropharyngeal swabs for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at the time of the BP diagnosis.Results No significant differences were found regarding COVID-19 infection and recovery from BP at the first, third, or sixth months of follow-up. According to the results, it seems that there is no association between COVID-19 infection and facial palsy; however, the patients infected with COVID-19 in the sample experienced a rapid, early recovery from BP. The mean incidence of BP in 5 years (2017–2021) was of 1.73/100 thousand individuals, with a statistically insignificant change throughout the years.Conclusion We were not able to show any association between BP and COVID-19. The patients underwent follow-up for up to 6 months, and we studied their patterns of recovery from BP, which were like those observed before the pandemic.
Keywords: Bell palsy; function recovery; COVID-19; facial nerve